Job satisfaction across different age groups and tenure at the City of Cape Town's department of social development and early childhood development - Eksteen, Rudi-Leigh (Department of Social Development, 2023)
Job satisfaction is an essential factor for all employers and the benefits of a satisfied workforce have been proven. Understanding what the key factors that promote job satisfaction and how this differs amongst different age groups and years in a position is the purpose of this research study. Exploring the association between job satisfaction, performance and retention was a further goal of this study. This qualitative study was conducted with an exploratory and descriptive research design and adopted purposive sampling of seventeen officials employed in the City of Cape Town's Department of Social Development and Early Childhood Development. All participants were interviewed individually using a semi-structured interview schedule and the data gathered was presented along with direct quotes from these interviews. The research study found that financial remuneration and benefits, management, organisation culture, nature of work, emotional exhaustion, intrinsic satisfaction and development were key factors to the participants in terms of their job satisfaction. Interestingly, those factors considered basic or lower order, while important do not provide satisfaction, but can cause dissatisfaction if deficits are perceived. Satisfaction is found in those factors considered higher order or motivators and herein the participants felt there was room for improvement. Several distinctions were found between when considering the influence of these factors amongst both age and tenure amongst the participants. Furthermore, associations between retention and job satisfaction were not as evident as those found been job satisfaction and productivity. Key recommendations made for the Department of Social Development and Early Childhood Development centred on clarity on job descriptions and the nature of work and a reassessment of training and development. Finally, the mental health of the officials needs to be viewed as a priority, with considerations around organisation culture, management and communication.